2000
DOI: 10.1590/s0004-27492000000400010
|View full text |Cite
|
Sign up to set email alerts
|

Manifestações oculares observadas em indivíduos infectados por HTLV-I no Rio de Janeiro

Abstract: Purpose: To evaluate the frequency of ocular manifestations observed in HTLV-I seropositive patients in Rio de Janeiro.Methods: The study included 17 patients with TSP/HAM (tropical spastic paraparesis/HTLV-I associated myelopathy) and 55 HTLV-I seropositive patients without TSP/HAM or ATLL (adult T-cell leukemia/lymphoma).Results: Regarding the TSP/HAM patient samples, we observed a frequency of 11.8% anterior uveitis, 11.8% retinal vasculitis and 5.9% vitreous opacity. In HTLV-I seropositive patients without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
2
6
1
1
Order By: Relevance
“…Similar to other reports, the presentation of HAU was mostly bilateral in our patients 18 and localized in the intermediate chamber 18,19 , with asymptomatic or oligosymptomatic presentations consisting of visual disturbances and oaters [18][19][20][21][22] . Changes in the anterior segment of the eye, vitreous cells, macular edema, epiretinal membranes, and abnormalities in retinal pigment distribution were also noted, in consonance with other reports in the literature [18][19][20][21][22] . However, in contrast, no retinal vasculitis was identi ed in the presently studied patients 19,21,22 .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Similar to other reports, the presentation of HAU was mostly bilateral in our patients 18 and localized in the intermediate chamber 18,19 , with asymptomatic or oligosymptomatic presentations consisting of visual disturbances and oaters [18][19][20][21][22] . Changes in the anterior segment of the eye, vitreous cells, macular edema, epiretinal membranes, and abnormalities in retinal pigment distribution were also noted, in consonance with other reports in the literature [18][19][20][21][22] . However, in contrast, no retinal vasculitis was identi ed in the presently studied patients 19,21,22 .…”
Section: Discussionsupporting
confidence: 89%
“…In the HTLV-1-uninfected control group, herpes simplex and tuberculosis were found to be associated with uveitis (Table 3). Other Brazilian studies investigating ophthalmologic changes in HTLV-1 reported a lower prevalence of HAU (from 1.9-2.85%) than that found herein (7.14%) [19][20][21][22] . However, unlike other reports 18, [20][21][22] , the present study was speci cally designed to determine the prevalence of HAU, and a comprehensive examination procedure was performed in all patients by a single investigator trained in the diagnosis of uveitis.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Indeed, prevalences of 1.93% and 1.82% in asymptomatic and HAM/TSP individuals, respectively, were observed in the City of Belo Horizonte, State of Minas Gerais, in the Southeast region of the country 30 . Only one study reported a prevalence of 11.8% of uveitis in TSP/HAM patients from Rio de Janeiro, also located in the same geographic region 34 . However, in this article, only the anterior uveitis was reported, in disagreement with most studies in Brazil and other countries where intermediate uveitis predominates 20 30 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that HTLV-1 infections are regarded as endemic in Brazil and highly prevalent in Bahia, Pernambuco and Pará, HTVL-1 and HTVL-2 infections are present in all regions, though with low prevalence among the general population (3,9) . ATLL pathogenesis, though not totally elucidated in humans, is linked with CD4T cell and HTLV-1 infections (17) and some risk factors such as the following : (1) gender, with higher prevalence among women due to their higher vulnerability to sexual transmission (4) ; (2) heredity, linked with higher genetic predisposition to the development of this type of leukemia (18) ; (3) direct correlation between the increase in atypical lymphocytes, proviral load and the aggravation of clinical symptoms (6,11,13) ; (4) low levels of serum HTLV-1 TAX antibody (escape mechanism of infected cells), inasmuch as in normal conditions TAX is able to cause intracellular changes in CD4+ lymphocytes and induce immunological response (5,10,16) ; (5) HTVL-1 vertical transmission via breast-feeding (1,2,18) .…”
Section: Introductionmentioning
confidence: 99%